The Animal Within : Creatures in (and outside) the mumok Collection - Ammer, Manuela; Müller, Ulrike; mumok - Museum moderner Kunst Stiftung Ludwig Wien (Köln : Verlag der Buchhandlung Walther und Franz König, 2022)
Samba, Chéri ; Ora Sherk, Bonnie ; Hohn, Ull ; Richier, Germaine ; Büttner, Werner ; Absalon, Hilde ; Eins, Stefan ; Bilda, Linda ; Rutherford, Erica ; Fahlström, Oyvind ; Christanell, Linda ; Haworth, Jann ; Niebuhr, Elly ; Moscouw, Michaela ; Karamustafa, Gülsün ; Joham, Isolde Maria ; Lam, Wifredo ; Graf, Franz ; Kowanz, Brigitte ; Knowles, Dominique ; Wenger, Susanne ; Talos, Kurt ; Friedmann, Gloria ; Kudo, Tetsumi ; de Saint Phalle, Niki ; Dicker, Friedl ; Orupabo, Frida ; Graves, Nancy ; Havliček, Karel ; Lassnig, Maria ; Weiler, Max ; Makavejev, Dušan ; Kelley, Mike
The Animal Within - Creatures in (and outside) the mumok Collection, mumok - Museum moderner Kunst Stiftung Ludwig Wien, Vienna, September 22, 2022 to February 26, 2023
boek